Range expansion method on heterogeneous network to increase picocell coverage - Hadi Supriadi; Hasanah Putri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this study, picocell planning was carried out on heterogeneous networks by applying the range expansion method. The case study was conducted in Coblong Subdistrict-Bandung on the 1800 MHz frequency. Heterogeneous network (HetNet) is a system that combines microcell networks and small cell networks (picocell and femtocell). The application of the range expansion method in picocell was aimed to broaden the scope of picocell. For the simulation, Atoll 3.3.0 software with observational parameters was implemented, including RSRP, SINR, throughput, and user connected. The planning results showed that the application of expansion method increased the coverage and quality of network, where the RSRP value ≥ -90 dBm was 97.72%, SINR ≥ 5 dB was 70.99%, uplink throughput was 17.80 Mbps, downlink throughput was 21.37 Mbps, and user connected was 99.2%.